Pengelolaan Limbah Medis Puskesmas Di Kabupaten Kupang Provinsi Nusa Tenggara Timur, Indonesia - Karolus Ngambut (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
The Public Health Center is a technical implementation unit of the health service in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 13 of 2015. This study aims to obtain baseline data on the amount of medical waste at the health center as a basis for implementing follow-up waste management. Survey of all Public Health Centers in Kupang Regency totaling 26 units of Public Health Centers. The results of the study showed that the characteristics of medical waste produced at the Public Health Center included sharp objects, varied. Efforts are needed to manage medical terminals at the Public Health Center that are compliant with waste management standards.